PERANCANGAN SISTEM KONTROL PIDAT PADA PLANT WATER LEVEL MENGGUNAKAN PLC (PROGRAMMABLE LOGIC CONTROLLER) - Listiana, Reni; Yurika, Yurika; Zakiyyannisa, Zahra (Jurnal TEDC; Vol 18 No 2 (2024): JURNAL TEDC, 2024)
In the industry, a good control system is needed in order to support the production process in the industry and to optimize efficiency in the production process. Controlling various process variables in production at the desired variable value is one of the important problems faced by the industry. Given this problem, it is necesssary to have a system that can control the variables as desired. In the industrial sector, PID (Proportional Integral Derivative) control is the most widely used because of its simple but effective controller structure for controlling linear systems. Plant water level is one of the control systems in the industry. This system is often found in the industrial world, for example PDAM (Regional Water Supply Company), oil refineries, and chemical factories. The operation of the plant water level in the Polytechnic TEDC Bandung SCADA lab still uses on-off control. The motor controlled by the inverter will stop if the water level in the main tank has reached the upper limit of the set point and motor will work if the water level in the tank is at the lower limit of the set point. This control has drawbacks because the controlled variables are only at two limits. The purpose of this study was to determine the effectiveness of the control system at the plant water level using a PID controller with the PIDAT instruction so as to know the correct PID parameter values to produce an accurate and fast quality control system. The set point water level is located in the main tank where there are three disturbance valves in the tank to disturb the stability of the set point. In maintaining the stability the stability of the set point by adjusting the flow, the PIDAT control process is carried out which utilizes the instructions in the PLC. Based on the test results of the plant water level control system using P and PIDAT control, PIDAT control is effective for obtaining PID parameters if the set point is not the same as the present value quickly and accurately. Because if you only use P control, the present value will not reach the desired set point. With the PID parameters obtained are P = 61, I = 61, and D = 9 with one disturbance valve, P = 43, I = 23, and D = 3 with two disturbance valves, P = 24, I = 5, and D = 1 with three distubance valves.